Exploring consumers’ intention to accept smartwatch - Wu, Liang-Hong; Wu, Liang-Chuan; Chang, Shou-Chi (Computers in human behavior, 2016)
With the growing smartwatch market over the past few years, smartwatch acceptance in consumer markets has become an important topic for both researchers and designers. Identification of factors that influence consumers to accept a smartwatch can improve user-centered design. This study explores the intentions of using a smartwatch from the consumer perspective, combining innovation diffusion theory (IDT), the technology acceptance model (TAM), the unified theory of acceptance and use of technology (UTAUT), and perceived enjoyment. It presents an integrated method empirically tested with data from 212 participants in Taiwan. Partial lease squares (PLS) were used for models and hypotheses tests. We find several interesting results greatly different from previous studies: (1) Attitude, often identified as a weak mediator, is significant; (2) Ease of use was not significant, which implies that it should be the basic specification of smartwatches; (3) Gender has no significant effect on acceptance of smartwatches; and (4) Individuals 35–54 years old exhibit a significant demand for enjoyment in their use of smartwatch. This study contributes to the technology acceptance research field, and identifies the characteristics that influence smartwatch acceptance. Our methods and results should benefit both academics and managers with useful suggestions for research directions and product strategies. •We explore customer intention to accept smartwatch.•We find several interesting results greatly different from previous studies.•Implications for researchers and developers are detailed.